Okra growth, yield and rhizosphere microbiome responses to the encapsulated bioinoculant application under reduced fertilization regime - Mohamad Roslan, Muhamad Aidilfitri; M. Sobri, Zulfazli; Tan, Ali Kee Zuan; Abdul Rahman, Nor Aini (MDPI AG, 2022)
There is limited evidence that Enterobacter hormaechei can improve plant physiology and yield through soil phosphate (P) and potassium (K) amelioration. This study unraveled the effect of different soil inoculation methods i.e., free-cell and encapsulated (alginate bead containing sugar-protein hydrolysate and molasses) E. hormaechei 40a with different rates of PK-fertilization on okra P and K uptake, and soil rhizosphere bacterial community. The results revealed that 3HB (half-dose PK-fertilizer + encapsulated strain 40a) had the highest soil available P (SAP) and K (SAK), as well as P and K uptake for all plant organs, followed by 3F (full-dose PK-fertilizer), 3HI (half-dose PK-fertilizer + free-cell strain 40a), and 3H (half-dose PK-fertilizer), and improved yield by up to 75.6%. Both inoculated and full-dose fertilizer treatments produced larger pods (>15 cm) compared to 3H. We discovered increased bacterial richness and diversity in both 3HB and 3HI samples compared to uninoculated treatments. Both 3HB and 3F treatments were positively correlated with the increasing abundance of Acidobacteriales, Burkholderia caballeronia paraburkholderia, Gemmataceae, and Sphingomonas along with the SAP and SAK. The plant-beneficial effect of one-time 3HB treatment on okra growth and yield was comparable to biweekly inoculation in 3HI, suggesting a new cost-effective farming approach in precision agriculture.